Development of Ethnoscience-based e-Worksheet to Stimulate Scientific Process Skills - Suyanto, Eko; Suyatna, Agus; Destryati, Annisya; Pratama, Afis (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
This study aims to develop an ethnoscience-based E-worksheet on sound waves topics that are valid and practical. The E-worksheet developed to stimulate students' science process skills was developed using the Flip PDF Professional application. This study employed Design and Development Research (DDR), which consisted of four stages: analysis, design, development, and evaluation. This ethnoscience-based E-worksheet contains material and practical guidance using Gamolan to investigate the sound waves topic with science process skills indicators, namely observing, formulating problems, formulating hypotheses, determining variables, collecting, processing, and concluding data. The E-worksheet was declared highly valid, with an average score of 3.6. Based on the analysis, the ethnoscience-based E-worksheet can be used to teach sound waves for the second semester of eleventh-grade high school students. The E-worksheet obtained a percentage of 93% in the very practical category based on the practical test by students and teachers. The students commented that the E-worksheet is appropriate for classroom learning, is interesting to read, and is equipped with videos that helped them in the learning process.